Design of a new t-way strategy for test case generation supporting sequence-less and sequence input interaction / Md Mostafijur Rahman - Rahman, Md Mostafijur (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
The aim of this research is to design and evaluate a new strategy based on t-way strategy, called t-way Input Interaction Test (TWIIT) which integrates both sequenceless and sequence input interaction. To fulfil the aim, the following objectives are taken under consideration ; to analyze recent research on t-way sequence-less and sequence input interaction based test strategies in order to identify the potential improvements, in designing tway test strategy ; to design and implement algorithm for TWIIT supporting sequence-less and sequence input interaction ; to evaluate the performance of TWIIT strategy with other competing strategies on the basis of the generated test suite size.